(3GdebUhOs - (3GdJjej, Gdchaj, CHh MfjaI, GdfYeGf Hf KGHJ, J (B150 (3g`s ((3eMeO Hf YHO GdQMje CafOj GdbTdGbjs)
(3ChdgG (B:s
(3GdMeO ddg GdhgGH ddeDefjf SHjd GdUhGH hGdUdGI hGdSdGe Ydi QShdg eMeO GdRGLQ Yf GdCPfGH (B((3cPG(B) ((3GdMGK(B) (3Ydi WdH GdKhGH CeG HYO aEf GdYQHjI hSjdI Edi GdYdhe GdTQYjI hCMO CQcGfgG GdJUQja dCfg jUjQ Gdbdjd ef GdCaYGd cKjQGs
(3BNQgG (B:s
(3hbO jchf aj HYV GdehGVY dG jJZjQ (B((3cPG(B) (3GdeYJdGJ ajg eY hLhO GdebJVj YhQ hGYJhQ hGSJhi hfMh Pdc aHYVgG dG JJZjQ dUMI GdHfGA hHYVgG dYdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 8 / 36s
(3eYLe GdeDdajf(B: 4 / 32s
(3cTa GdXfhf(B: 2 / 1806s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdUQas